(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article notes that two straight – disc drives are installed in front of the channel excavator in order to improve the irrigation, thus reducing the quality of the channel excavation. During the excavation, due to partial disintegration of the soil layer due to rotational movement of the disсs, the slope of the ditch is maintained at the required level and interrupted the problem of maintaining the uniformity of the ditch sidewall. n recent years, some unmanned operation systems for the hydraulic excavator are required and some systems arealready developed. However, it is difficult to realize effective operation utilizing such systems, because the operator cannot sense ground condition. The skillful operator adaptive their operation to the excavating environment based on the experience, and realizing the efficient excavating. In this paper, we described the experiment for extracting operator’s skill for controlling unmanned hydraulic excavator. We compare the operation of skillful with non-skillful operator and discuss the result for the modeling of operator’s skill. From these results, we have revealed that skillful operator realizes unified trajectories of the bucket with quick moving and this causes the efficient performance